1987
DOI: 10.1016/0014-5793(87)80125-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin‐like growth factor‐I and ‐II genes in rat medullary thyroid carcinoma

Abstract: Several types of cancer cells produce polypeptide growth factors and often the same cells have functional receptors for the released growth factor (autocrine secretion). We have studied expression of genes encoding somatomedin-C/insulin-like growth factor-I (Sm-C/IGF-I) and IGF-II, in rat medullary thyroid carcinomas (MTCs) in different stages of tumour differentiation. RNAs hybridizing specifically to an IGF-I cDNA probe were detected in 6 out of 7 differentiated MTCs and IGF-II related RNAs were demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…These include Wilms' tumor, rhabdomyosarcoma, adrenal pheochromocytoma, medullary thyroid carcinoma, leiomyosarcoma, hepatoma, liposarcoma, and breast carcinoma (Reeve et al, 1985;Scott et al, 1985;Haselbacher et al, 1987;Hoppener et al, 1987;Daughaday et al, 1988;Su et al, 1989;Tricoli et al, 1986;Yee et al, 1988). Several of these hu- man tumors synthesize both IGF-I and IGF-I1 mRNA (Daughaday et al, 1988;Su et al, 1989;Hoppener et al, 1987) as in the case of colorectal tumors taken from patients at surgery (Tricoli et al, 1986). However, recent studies have shown that the levels of IGF-I1 mRNA and protein are not necessarily correlated (Haselbacher et al, 1987;Graham et al, 1986).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These include Wilms' tumor, rhabdomyosarcoma, adrenal pheochromocytoma, medullary thyroid carcinoma, leiomyosarcoma, hepatoma, liposarcoma, and breast carcinoma (Reeve et al, 1985;Scott et al, 1985;Haselbacher et al, 1987;Hoppener et al, 1987;Daughaday et al, 1988;Su et al, 1989;Tricoli et al, 1986;Yee et al, 1988). Several of these hu- man tumors synthesize both IGF-I and IGF-I1 mRNA (Daughaday et al, 1988;Su et al, 1989;Hoppener et al, 1987) as in the case of colorectal tumors taken from patients at surgery (Tricoli et al, 1986). However, recent studies have shown that the levels of IGF-I1 mRNA and protein are not necessarily correlated (Haselbacher et al, 1987;Graham et al, 1986).…”
Section: Discussionmentioning
confidence: 92%
“…A number of tumors appear to express elevated levels of IGF-I1 mRNA. These include Wilms' tumor, rhabdomyosarcoma, adrenal pheochromocytoma, medullary thyroid carcinoma, leiomyosarcoma, hepatoma, liposarcoma, and breast carcinoma (Reeve et al, 1985;Scott et al, 1985;Haselbacher et al, 1987;Hoppener et al, 1987;Daughaday et al, 1988;Su et al, 1989;Tricoli et al, 1986;Yee et al, 1988). Several of these hu- IGF-II(o), insulin (m), and 7.5 K-peak (0) on specific binding of '"51-IGF-11 to HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several molecular species of IGF-I have been reported for rat thyroid medullary carcinoma tissue, ranging in size from 1 to 7 Kb approximately [73], in our experimental conditions, hybridisation of the IGF-I specific probe to a thyroid RNA species of approximately 1000 nucleotides was documented.…”
Section: Igf-i/igf-ir Expression In Thyroid Neo-plasmsmentioning
confidence: 95%
“…Thesubunit of IGF-1R binds IGF-I, IGF-II, and insulin at supraphysiological doses; the -subunits contain the TK domain [122]. IGF-II and IGF-1R are overexpressed in many cancer types, including MTC [123]. IGF-1R up-regulation was found to mediate resistance to TKIs in different types of cancer cells.…”
Section: Insulin-like Growth Factor Receptor Pathwaymentioning
confidence: 99%
“…IGF-I and IGF-1R are over-expressed in thyroid cancer, particularly in the most aggressive variants [124]. Importantly, IGF-I and insulin are essential for the mitogenic action of TSH and EGF in thyroid follicular cells [123]. ADW742 is a specific inhibitor of IGF-1R phosphorylation and of its signaling pathway.…”
Section: Insulin-like Growth Factor Receptor Pathwaymentioning
confidence: 99%